Students' Perception of the Practicality of Integrated Chemistry Learning Media Technological Pedagogical Content Knowledge and Culturally Responsive Transformative Teaching Model - Irma Rahayu Lestari; Wahyu Zahraini; Muntari Muntari; Mutiah Mutiah (Indonesian Publication Center, 2023)
This qualitative descriptive research aims to compare the perception of male and female students in grade X of high school toward the practicality of chemistry learning media that integrates Technological Pedagogical Content Knowledge (TPACK) and Culturally Responsive Transformative Teaching (CRTT). This research was carried out at SMAN 1 Narmada with a research sample of 36 students in class X. Perception data was collected using a closed questionnaire includes three aspects of assessment, namely the aspect of presentation, ease of use, and benefits of learning media, by distributing the questionnaire offline to respondents. The data analysis technique of the student perception questionnaire uses descriptive statistical data analysis. The results obtained showed that the average value of students’ perception of the practicality of chemistry learning media was reviewed based on the perception of male students in terms of presentation, ease of use, and benefits respectively, namely 84%, 82%, and 84% with an average of 83% included in the practical criteria, while the perception of female students was obtained by 83%, 82%, and 85% respectively with an average of 83% included in the practical criteria. Based on the results of the study, it can be concluded that there is no significant difference between the perception of male and female students towards the practicality of TPACK and CRTT integrated chemistry learning media on the topic of chemical bonding.